EXPERIMENTAL AND THEORETICAL STUDY OF SHYNTESIS OF N-ALKYL-NITROIMIDAZOLES. - SALAMANCA M., Constain; TIZNADO V., William; JARAMILLO G., Paula (Vitae, 2010)
In this work we realized and experimental and theoretical study of the N-alkylation of nitroimidazoles. The N-alkyl-2-methyl-nitroimidazoles correspond to biologically active molecules, obtained by reaction of 2-methyl-5-nitroimidazole and different alkyl halides. This reaction showed the formation of a mixture of isomeric products in different proportions, denominated like N-alkyl-2-methyl-4-nitroimidazole and N-alkyl-2-methyl-5-nitroimidazole, respectively. The reaction suggestes the formation of a tautomeric equilibrium, which generates two nucleophilic sites susceptible to electrophilic attack by the alkyl halide. The local nucleophilic reactivity of the nitroimidazole ring is determined using local reactivity indices such as the Fukui function and the electrostatic potential, besides the electronic localization function (ELF). The Fukui function was integrated for each atom using partition schemes based on analysis of Mulliken charges and natural bond orbital (NBO). Finally the reaction profiles were assessed. The results show a minor difference in the local reactivity. Nevertheless a significant difference in energy barriers is observed explaining the formation of an isomeric product over another. These results agree quite well with the experimental data.